2021
DOI: 10.3390/su13147713
|View full text |Cite
|
Sign up to set email alerts
|

Determining Factors of Psychological Performance and Differences among Age Categories in Youth Football Players

Abstract: Within the determining factors of psychological performance, mental toughness is considered a multidimensional factor, comprising cognitive, affective, and behavioural components together with self-confidence, which is related to success in sports performance as well as psychological health and well-being. The aim of this study was to analyse the relationship between different factors composing mental toughness and age categories in young football players, in order to determine the presence of specific psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In the increasingly fierce sports competition, the role of psychological training has become increasingly prominent. 9 The usual technical, tactical and physical training is not systematic and step-by-step. Coaches often only focus on the psychological preparation before the game, ignoring long-term psychological training.…”
Section: Lack Of Systematic and Targeted Psychological Trainingmentioning
confidence: 99%
“…In the increasingly fierce sports competition, the role of psychological training has become increasingly prominent. 9 The usual technical, tactical and physical training is not systematic and step-by-step. Coaches often only focus on the psychological preparation before the game, ignoring long-term psychological training.…”
Section: Lack Of Systematic and Targeted Psychological Trainingmentioning
confidence: 99%
“…The most prevalent research areas in the field of women’s football have been related to sports medicine, followed by physiology and sociology (society, patterns of social relationships, social interaction, and culture; Kryger et al, 2021 ). Psychological factors have received less attention, although there is a clear consensus regarding the importance of mental strength to athletes’ performance ( Fletcher and Sarkar, 2012 ; Herrero et al, 2021 ; Sillero et al, 2021 ). A recent systematic review found that there were only 14 studies examining the relationship between performance and psychological factors in female football players ( Pettersen et al, 2021 ), while a review article identified only six articles that investigated sport psychology in elite-level female soccer players ( Kirkendall and Krustrup, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, (Gucciardi et al, 2017) show that in terms of strength, skill, and will to win, 90% of the critical success factors depend on mental aspects. Strictly speaking Gould et al (Benítez-Sillero et al, 2021) also say that 82% of coaches state that mental strength is a determining factor in achieving sporting success. One of the factors that can affect achievement is the motivation factor.…”
Section: Introductionmentioning
confidence: 99%